Analysis of Global Value Chains: Indonesia’s Pearl Industry Competitiveness - Ufairah; Aisyah, Sari Mutiara (Cendekia Niaga, 2024)
As global value chain practices continue to spread worldwide, concerns about competitiveness emerge within prevailing policies, emphasizing long-term productivity and attractiveness. Indonesian South Sea pearls embody both economic potential and challenges affecting their bargaining power. This research aims to present a comprehensive overview of the Indonesian government's efforts to enhance south sea pearl’s competitiveness. Utilizing global value chain analysis, it explores the policies implemented by both central and local authorities to enhance the pearl industry's competitiveness, investigating their impact on company governance and upgrading practices through a focused case study on NMJ LLC. Results underscore substantial strides where the central government establishes legal foundations and enhances South Sea pearls quality. While the local government focuses on improving productivity in both downstream and upstream sectors. Additionally, both levels of government facilitate platforms for global market access. Moreover, the NMJ LLC case study analysis underscores policy implementation’s influence on its governance and upgrading, classified as retail buyer-driven value chain governance and product upgrading, respectively.